Atheroprotection by 11β-HSD1 inhibition in apolipoprotein E knockout mice is associated with lowering of blood pressure. (22nd September 2015) - Iqbal, J; Sullivan, K; Livingstone, DE; Andrew, R; Walker, BR; Hadoke, PWF
Abstract : Introduction: Tissue-specific metabolism of glucocorticoids by the isozymes of 11β-hydroxysteroid dehydrogenase (11β-HSD) has been implicated in the pathogenesis of atherosclerosis. 11β-HSD type 1 regenerates glucocorticoids in target tissues and is under investigation as a therapeutic target in type II diabetes and the metabolic syndrome. Selective inhibition of 11β-HSD1 in atherosclerosis-prone mice dramatically reduced lesion development in one study (Hermanowski-Vosatka et al, 2005) but the mechanisms involved remain controversial. This study aimed to determine whether 11β-HSD1 inhibition reduces atherogenesis by the improvement of cardiovascular risk factors. Methods: Adult male apolipoprotein E (Apo-E) knockout mice (n  =  6/group) were fed an atherogenic western diet for 6 weeks and then randomly assigned to either no treatment (control group) or selective 11β-HSD1 inhibition (using 3-(1-adamantyl)-6, 7, 8, 9-tetrahydro-5H-[1, 2, 4]triazolo[4, 3-α]azepine; 10 mg/kg per day administered in food), while the western diet was continued for a further 8 weeks. Body weight and systolic blood pressure (tail cuff plethysmography) were measured during treatment and, at the end of the study, fasting biochemistry and glucose tolerance/insulin sensitivity were assessed by glucose tolerance test (2 mg/g glucose intraperitoneally). The extent of atherosclerotic lesion development was assessed at the end of the treatment period by semiquantitative assessment of lesion distribution throughout the arterial tree. Lesions were graded from 0 to 5, in which grade 0 was no lesion and grade 5 was a totally occlusive lesion. Data, mean ± SEM, were analysed using GraphPad Prism. Results: Mice treated with the 11β-HSD1 inhibitor resisted weight gain on the western diet (0.8 ± 0.4 g vs 1.9 ± 0.2 g, p = 0.03) and had significantly lower systolic blood pressure (106 ± 1.4 mm Hg vs 118 ± 1.1 mm Hg; p⩽0.0001). There was no significant difference in glucose and insulin levels on the glucose tolerance test (area under the curve (AUC)Glucose 50 100 ± 4448 mg/dl per minute vs 54 630 ± 1504 mg/dl per minute, p = 0.3573 and AUCInsulin 71.64 ± 14.71 ng/ml per minute vs 108 ± 15.2 ng/ml per minute, p = 0.1166) or plasma cholesterol levels (13.2 ± 1.5 mmol vs 12.0 ± 1.6 mmol, p = 0.2330) following 11β-HSD1 inhibition. Atherosclerotic lesion development was reduced in mice treated with the 11β-HSD1 inhibitor, with significantly less plaque formation in all major vessels expressed here as global atheroma grade (3.0 ± 1.0 vs 3.6 ± 0.9, p = 0.03). Conclusion: This investigation confirms the ability of 11β-HSD1 inhibition to reduce the development of atherosclerotic lesions in mice. Assessment of cardiovascular risk factors suggests, however, that the reduced lesion size is associated with reduced blood pressure and subtle beneficial changes in glucose/insulin homeostasis. Hypertension occurs with increased angiotensinogen when 11β-HSD1 is overexpressed in adipose tissue and in the liver, a converse mechanism may contribute to atheroprotection with 11β-HSD1 inhibition.